2013
DOI: 10.1371/journal.pone.0073733
|View full text |Cite
|
Sign up to set email alerts
|

Defeating Crypsis: Detection and Learning of Camouflage Strategies

Abstract: Camouflage is perhaps the most widespread defence against predators in nature and an active area of interdisciplinary research. Recent work has aimed to understand what camouflage types exist (e.g. background matching, disruptive, and distractive patterns) and their effectiveness. However, work has almost exclusively focused on the efficacy of these strategies in preventing initial detection, despite the fact that predators often encounter the same prey phenotype repeatedly, affording them opportunities to lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 29 publications
2
73
1
Order By: Relevance
“…The experiment used a block design: each of the 7 different target types was presented in a random order in one block, and the full experiment contained 20 blocks, meaning that each participant made 140 capture attempts in total, and each target type was presented 20 times throughout the experiment. We used this number of blocks as it gave a comparable number of target presentations to other studies where learning effects have been seen [33]. Figure 1 shows an example screen shot from this experiment.
Figure 1 An example screen shot showing the general set up of the experiment.
…”
Section: Methodsmentioning
confidence: 99%
“…The experiment used a block design: each of the 7 different target types was presented in a random order in one block, and the full experiment contained 20 blocks, meaning that each participant made 140 capture attempts in total, and each target type was presented 20 times throughout the experiment. We used this number of blocks as it gave a comparable number of target presentations to other studies where learning effects have been seen [33]. Figure 1 shows an example screen shot from this experiment.
Figure 1 An example screen shot showing the general set up of the experiment.
…”
Section: Methodsmentioning
confidence: 99%
“…Camouflage is a classic example of evolution through natural selection, and the selective advantage of cryptic phenotypes in avoiding predation has received considerable attention in recent years (Vignieri et al 2010;Chiao et al 2011;Zylinski and Johnsen 2011;Troscianko et al 2013). A widespread camouflage strategy is background matching, whereby an animal closely resembles its surroundings in color, brightness, and pattern (Stevens and Merilaita 2009a).…”
Section: Introductionmentioning
confidence: 99%
“…First, it could be due to the coarse scale at which we investigated the association between habitat and plumage patterns. Many of the empirical studies that demonstrate a camouflage function of patterns in non-colour changing animals show an association in one or a limited number of species (e.g., Lovell et al, 2013; Kang et al, 2014; Marshall, Philpot & Stevens, 2015b.; Wilson-Aggarwal et al, 2016) or were found via predator–prey computer simulations (e.g., Stevens, Yule & Ruxton, 2008; Stevens et al, 2011; Scott-Samuel et al, 2011; Troscianko et al, 2013; How & Zanker, 2014; Hughes, Troscianko & Stevens, 2014; reviewed in Marshall & Gluckman, 2015). At the level of microhabitats, some studies demonstrate that individual behaviours may facilitate camouflage, such as a behavioural choice to rest on backgrounds that enhance camouflage (Tsurui, Honma & Nishida, 2010; Lovell et al, 2013; Kang et al, 2014; Marshall, Philpot & Stevens, 2015b.; Troscianko et al, 2016; Wilson-Aggarwal et al, 2016).…”
Section: Discussionmentioning
confidence: 99%